2016
DOI: 10.1177/0022146516660343
|View full text |Cite
|
Sign up to set email alerts
|

Uncertain Expertise and the Limitations of Clinical Guidelines in Transgender Healthcare

Abstract: To alleviate uncertainty in the specialized field of transgender medicine, mental and physical healthcare providers have introduced the rhetoric of evidence-based medicine (EBM) in clinical guidelines to help inform medical decision making. However there are no diagnostic tests to assess the effectiveness of transgender medical interventions and no scientific evidence to support the guidelines. Using in-depth interviews with a purposive sample of 23 healthcare providers, I found that providers invoked two stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 22 publications
1
61
0
Order By: Relevance
“…Medical gatekeeping entails control over access to healthcare resources or information. Although gatekeeping may occur at various points of health service delivery, including information flow among clinical staff (Riley and Manias , Street ), reluctance or refusal to order certain screening tests or treatments (Faulkner 2002, Shuster , Tritter et al . ), and pharmacists’ ethical decision‐making (Chiarello ), most sociological studies have focused on practices that facilitate or constrain patients’ entry to care.…”
Section: Sociological Approaches To Medical Gatekeepingmentioning
confidence: 99%
“…Medical gatekeeping entails control over access to healthcare resources or information. Although gatekeeping may occur at various points of health service delivery, including information flow among clinical staff (Riley and Manias , Street ), reluctance or refusal to order certain screening tests or treatments (Faulkner 2002, Shuster , Tritter et al . ), and pharmacists’ ethical decision‐making (Chiarello ), most sociological studies have focused on practices that facilitate or constrain patients’ entry to care.…”
Section: Sociological Approaches To Medical Gatekeepingmentioning
confidence: 99%
“…This statement is in accord with Davy's (2015) research on the politics of diagnosing trans people, where it was found that the diagnostic framework in the DSM-5 draws upon a binary conception of gender and judges trans people according to their wish to align their genitals with their gender identity through gender-confirming surgery. The view that trans people are interpreted against this backdrop as having a similar trans experience outlined by Shuster (2016) is made apparent in the above statement. What also became evident in the comments of a few practitioners is that there is insufficient updated scientific information available on trans identities and embodiments who do not fit in the authentic trans ideal and that this has a considerable impact on their practice with people who do not position themselves within the gender binary.…”
Section: Struggling and Accepting Gender Non-conformitymentioning
confidence: 81%
“…This practitioner, like others who follow a social model, adopts a position which understands gender identity as fluid and therefore allows room for the diagnostic attribution of GD to people who do not correspond to the authentic trans identity (McQueen 2016). Without biomarkers or scientific tests to prove the diagnosis of GD (Shuster 2016), making decisions on the diagnostic attribution based on the identification of the authentic trans identity (McQueen 2016) is problematic as it relies on the assumption of the existence of a real man and woman (Hird 2002) and, therefore, constrains the validation of other forms of identity, apart from the normative gender binary, by practitioners. What this also means is that without the diagnosis of GD some trans people might not access gender-confirming medical procedures; even when trans people do not intend to do genital surgery, they might wish to undergo other gender-confirming medical procedures such as breast surgery or hormone therapy.…”
Section: The Alignment Of the Body And Gender Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…To this end, each of the articles in this special issue builds upon recent insights from emerging transgender studies in sociology. Recent sociological studies, for example, consistently demonstrate that transgender people face significant inequalities in familial (Meadow ; Pfeffer ; Travers ) ; religious (Moon, Tobin, and Sumerau ; Sumerau, Mathers, and Cragun ; Sumerau, Mathers, and Lampe ); occupational (Connell ; Schilt ; Yavorsky ); medical (Johnson ; Lampe, Carter, and Sumerau ; Shuster ); and public (Abelson ; Mathers ; Rogers ) contexts. They also demonstrate difficulties and resistance transgender people experience when seeking to negotiate and present non‐cisgender identities in public and private interactions (Darwin ; Garrison ; Shuster ).…”
mentioning
confidence: 99%